PENYUSUNAN PAKET WISATA PADA CV. BILAVA TOUR TRAVEL DI PEKANBARU - Tifanny Yolanda; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this research is to analyze and find out the types of tour packages available and the Mechanism of Preparing Tour Packages at CV. Bilava Tour Travel in Pekanbaru. The research method used to write this research is qualitative. The results showed that: Types of tour packages offered at CV. Bilava Tour Travel in Pekanbaru, namely Ready Made Tour and Tailored Made Tour. Then for preparing tour packages on CV. Bilava Tour Travel in Pekanbaru went through three planning stages, namely collecting data/observations, identifying work partners, and making detailed tour package prices. The preparation of this tour package aims to travel inbound, outbound, and domestic. The target market for preparing tour packages in CV. Bilava Tour Travel namely Individual tours, Family groups, and Group tours. Companies and schools are the most frequently used target market for tour packages. Companies to carry out Employee Gathering activities and special schools for outings, study tours / comparative studies. Keyword: Tour Packages, Tourists, Bilava Tour Travel